2001
DOI: 10.1145/1037107.1037114
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive per-host IP paging architecture

Abstract: IP Paging has received considerable attention recently . Th e IETF has decided to develop an IP Paging protocol an d some IP Paging protocols have been proposed by researcher s [13,12] . However all of these proposals use static and manually configured paging areas . We argue that the size and the shape of paging areas are very critical for the performance of a paging system . A system that allows each hos t to use a paging area that adapts to its mobility and communication patterns will perform better . This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…In [11], the authors proposed a practical solution for adaptive Individual IP Paging by sharing load of configuration and calculation between the network and MHs. More precisely, the optimal PA size is computed per-host while the PA shape is constructed based on the aggregate mobility patterns of all MHs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [11], the authors proposed a practical solution for adaptive Individual IP Paging by sharing load of configuration and calculation between the network and MHs. More precisely, the optimal PA size is computed per-host while the PA shape is constructed based on the aggregate mobility patterns of all MHs.…”
Section: Related Workmentioning
confidence: 99%
“…Individual paging: Individual paging schemes are motivated by the observation that mobility and communication patterns of MHs may vary, and thus, a paging scheme adaptive to each individual MH would perform more efficiently. In individual paging, paging schemes may differ to one another in the way they are adaptive as presented in [2] and [11].…”
Section: Paging Schemesmentioning
confidence: 99%
“…However, they mentioned that the use of IP multicast might be a possible solution, but more works are required, especially for dynamic paging areas or selective paging schemes. In [13], they mentioned the use of small group multicast (SGM), which is similar to xcast. However, in this work, since a PA is dynamically constructed by the determination of MH, it results in high computation overhead and energy consumption of the MH.…”
Section: Ip Paging Protocolmentioning
confidence: 99%
“…Several studies on IP paging have been progressed for determining the paging area size dynamically [7,8,9]. However, those studies considered the speed of MN only at the calculation of the paging area size and suggested that the paging area size of MN should expand as its speed increased,…”
Section: Introductionmentioning
confidence: 99%